2016
DOI: 10.1097/sle.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

One-year Surgical Outcomes and Costs for Medicaid Versus Non-Medicaid Patients Undergoing Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Purpose To compare one-year outcomes and costs between severely obese Medicaid and non-Medicaid patients who underwent laparoscopic Roux-en-Y gastric bypass surgery. Methods Single institution, retrospective review comparing 33 Medicaid patients to 99 randomly selected non-Medicaid patients (1:3 case-control). 90-day and one-year outcomes were extracted from the electronic health record. Costs were obtained from the UW information technology division. Bivariate analyses were used to compare study variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Baseline. Our study further substantiates the existing body of evidence (13)(14)(15)(16)(17) that has suggested that Medicaid patients present for surgery with a greater burden of comorbid disease despite representing a slightly younger population. All but two comorbidities were more common among Medicaid patients.…”
Section: Period-specific Differencessupporting
confidence: 87%
“…Baseline. Our study further substantiates the existing body of evidence (13)(14)(15)(16)(17) that has suggested that Medicaid patients present for surgery with a greater burden of comorbid disease despite representing a slightly younger population. All but two comorbidities were more common among Medicaid patients.…”
Section: Period-specific Differencessupporting
confidence: 87%
“…Despite these baseline differences, four of the seven studies reported similar proportions of weight lost at follow‐up among Medicaid and commercially insured patients . Three studies reported less weight loss in Medicaid recipients.…”
Section: Resultsmentioning
confidence: 93%
“…All seven studies reporting on weight outcomes observed a substantial weight reduction in all insurance groups . The reported outcome variables included the percent of excess weight lost, difference in weight or BMI between time points, and weight loss classified as suboptimal (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations